Go ask your mothers one simple step for managers to support working moms for team success - Wells, Sarah 1980- (Ascent Audio, 2024)
From a CEO of a multi-million-dollar company that empowers working moms, this guide gives managers an inside look at what mothers really want from their leaders. In a post-pandemic job market, creating a truly mom-supportive workplace is the ultimate competitive advantage. But there's a pervasive problem across workplaces big and small: Managers aren't asking new mothers what support they need to transition back to work successfully. At the same time, working moms are afraid to ask for help-resulting in poor employment outcomes for both parties.
Online resource; title from title details screen (O'Reilly, viewed October 29, 2024)
Keywords: Working mothers; Women -- Employment re-entry; Personnel management; Mères au travail; Femmes; Retour sur le marché du travail; Personnel; Direction; Audiobooks; Livres audio